Knowledge transfer in heritage cultural craft, damask weaving - Jönsson, Clary (FormAkademisk, 2021)
The hand weaving of damask is no longer a craft that is commonly learned and very few books on the subject have been published in the last century. Damask weaving still exists among private practitioners, but what happens to the knowledge when nobody knows how to dress a loom and weave anymore? The aim of this study is to describe and compare damask weaving from a learning perspective in order to generate knowledge of how damask weaving is described in the literature and how the knowledge is communicated to increase understanding of the learning process and to generate a theoretical understanding of practical knowledge transfer. The method used is a literature study and open interviews with people who teach damask weaving. The study shows that the literature does not provide enough information on how to dress and weave damask. The interviews give a deeper understanding of the practical knowledge. The analysis shows that it is difficult to use only cognitive reading as interpretation from the body and hands are needed and the different steps need to be dissected in detail.